RESPONSE SURFACE METHOD-BASED OPTIMIZATION OF OUTER ROTOR PERMANENT MAGNET SYNCHRONOUS MOTOR - Rafiee, Vahid; Faiz, Jawad (Journal of Energy Technology, 2024)
The Finite Element Method (FEM) is a prominent analysis approach. Although it is applicable for simulation and optimization of electrical machines, FEM is a very time-consuming technique. One of theapproaches to shorten the optimization runtime is the use of surrogate models instead of FEM. In this paper, the design and optimization of an outer rotor permanent magnet synchronous motor for ahybrid vehicle are investigated. Response surface methodology (RSM) with four input variables is integrated with a sequential quadratic programming algorithm for optimization. Before the optimization,the performance of the surrogate model in the prediction of untried points is validated. Finally, the optimal motor is simulated by FEM to verify the results of RSM-based optimization, and the outputsof both models are compared.